X-ray crystal structure analysis of 5-bromospiro[indoline-3,7’-pyrano[3,2-C:5,6-C’]dichromene]-2,6’,8’-trione - Sharma, Varun; Banerjee, Bubun; Kaur, Gurpreet; Gupta, Vivek Kumar (European Journal of Chemistry, 2021)
An analog of spirooxindole[pyrano-bis-2H-l-benzopyran] derivatives namely 5-bromospiro [indoline-3,7’-pyrano[3,2-c:5,6-c’]dichromene]-2,6’,8’-trione was synthesized via one-pot pseudo three-component reaction of one equivalent of 5-bromoisatin and two equivalents of 4-hydroxycoumarin using mandelic acid as a naturally occurring organo catalyst in aqueous ethanol under reflux conditions. The synthesized compound was characterized by FT-IR, 1H NMR, 13C NMR, and HRMS data. Crystal structure was determined by using single X-ray crystallography technique. It was found that the crystals are triclinic with space group P-1, C108H60Br4N4O29S2: a = 11.8333(6) Å, b = 12.8151(6) Å, c = 17.1798(8) Å, α = 77.317(4)°, β = 74.147(4)°, γ = 66.493(5)°, V = 2280.0(2) Å3, Z = 1, T = 149.99(10) K, μ(MoKα) = 1.902 mm-1, Dcalc = 1.647 g/cm3, 11545 reflections measured (3.836° ≤ 2Θ ≤ 50.998°), 8310 unique (Rint = 0.0488, Rsigma = 0.0875) which were used in all calculations. The final R1 was 0.0622 (I > 2σ(I)) and wR2 was 0.1994 (all data). The crystal structure was solved by direct methods and refined by full-matrix least-squares procedure to a final R-value of 0.0622 for 6264 observed reflections. The crystal structure was stabilized by an elaborate system of N-H···O, O-H···O, C-H···π, and π···π interactions involving solvent molecules to form supramolecular structure.